PROXIMATE AND MICROBIAL ASPECTS OF DONKEY (EQUUS ASINUS) BILTONG IN BOTSWANA - MOTSUMI, LEUTLWETSE (Bloemfontein: Central University of Technology, Free State, 2016)
Research on donkey meat and meat products has been overlooked for a long time even though there is considerable global research focused on horse meat. Recent literature is limited to investigations exploring the nutritional value of donkey meat (Aganga et al., 2003), and very little information is available on people’s knowledge, attitudes, beliefs and practices (KABP), or on the microbial and chemical contents of donkey meat and meat products. In this study, an overall view on the KABP as well as on the microbial and physico-chemical aspects of donkey meat and biltong was acquired in Kanye, Botswana, within six selected districts where donkey meat is used over other species of meat. The knowledge of food handlers and meat processors regarding hygiene, food safety and meat legislation, together with opinions on business performance, availability of equipment and facilities in meat processing plants, was assessed. The survey included total of 285 respondents in the Southern, Kweneng and Central districts of Botswana of which 280 were consumers. Proximate analysis of related parameters and profiles of Staphylococcus aureus, Escherichia coli, Bacillus cereus, Salmonella spp, total viable counts (TVC), yeasts and moulds on both fresh meat and biltong were assessed. Two donkeys from Banyana farms were slaughtered in a period of two months and from each, two fresh meat samples and one sample for biltong were taken. The highest mean TVC counts recorded were for donkey 1. The mean values of Staphylococcus aureus counts detected from donkey 1 samples from the forequarter were 1.6x101, hindquarter 0, and donkey 2 mean values were 3.3X10-1 (forequarter), 1.5x104 - 8.16x103 (hindquarter) and 2.3x102 – 7x101 (biltong). In general, meat samples did not show high loads of bacteria; however the biltong showed presence of Staphylococcus aureus. The mean microbial load on the fresh meat ranged from 1.0x10¹ to 3.5X10² cfu.g-1 while loads on the biltong sample ranged between 1.26X10⁶ and 6.5X10³ cfu.g-1. To prevent bacterial contamination, meat and meat products such as biltong must be handled and packed properly in sterilised polyvinyl containers. On the other hand, total fat, total ash, moisture content and water activity were measured and recorded at 2.8 of fat, 4.38 of ash, 24.65 of moisture and 0.998 (aw) for the forequarter of donkey 1. The hindquarter of the same donkey recorded 12.26 (fat), 3.81 (ash), 23.72 (moisture) and 0.999 (aw). Moreover, for donkey biltong from donkey 1, 15.31 (fat), 9.29 (ash), 84.37 (moisture) and 0.654 (aw) were recorded. The donkey 2’s samples were 28.48 (fat), 7.31 (ash), 30.02 (moisture) and 0997 (aw) for the forequarter, with the hindquarter of this donkey recording 44.6 (fat), 5.29 (ash), 33.5 (moisture) and 0.998 (aw). Finally, 11.66 (fat), 5.26 (ash), 69.84 (moisture) and 0.668 (aw) were recorded for biltong product produced from donkey 2. Extensive scope still exists for research into the microbiology and nutritional value of donkey meat especially in the light of great interest in donkey meat in arid areas such as Botswana and other Southern regions. In conclusion donkey meat (both fresh and biltong) is just like other red meats.
Published Thesis